Optimization of Polysorbate 80 and Sorbitan Monooleate 80 aas Emulsifiers in Foundation Makeup Containing Ethyl Cinnamate - Ungsari Rizki Eka Purwanto; Intan Martha Cahyani; Yuliana Purwaningsih; Berliana Ganita Fatika Sandhi; Fitria Febryana (Indonesian Journal of Pharmacy, 2023)
Cosmetic foundation is a type of decorative makeup and commonly include a sunscreen agent. Ethyl cinnamate is one of the potential organic essential oil sunscreens. Nevertheless, there is little study on ethyl cinnamate usage in cosmetics, particularly oil-in-water foundation cream. Using an emulsifier in oil-in-water foundation cream a higher concentration does not guarantee higher oil phase recovery. However, using two combinations of emulsifier such as polysorbate 80 and sorbitan monooleate 80 with the optimum combination can be the right solution. This study aims to optimize polysorbate 80 and sorbitan monooleate 80 in a cream foundation using ethyl cinnamate as an active ingredient designed to have an effective ability to protect facial skin from ultraviolet radiation and are safe to use. The optimization formulas design of the emulsifier combination in foundation cream was made using the Simplex Lattice Design method with help Design Expert version 10.0.1. Parameter optimization were the value of pH, viscosity, spreadability, adhesion, and Sun Protection Factor (SPF) value. The stability test and skin irritation test of optimum formula were also conducted. As a positive control, Revlon Colorstay Foundation as a brand cosmetic foundation was used (National Food and Drug Agency of Indonesia number : NA18140300519). The optimum ratio of polysorbate 80 and sorbitan monooleat 80 were 9.565 and 1.435 with the physical characteristics of pH 6.478+0.008; viscosity 5844.2+31.82 cPs; spreadability 6.16+0.11 cm; adhesion 3.346+0.14 seconds; SPF Value 22.385+0.48, and no irritation symptoms. The ethyl cinnamate foundation created was physically stable, had a pleasing look, and did not irritate the skin, making it safe to wear. It also provides efficient UV radiation protection.